(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The interactive microgroup method has emerged as a progressive pedagogical approach in physical education, aimed at improving student engagement, teamwork, and academic achievement. This study examines the effectiveness of this method in improving students’ physical skills, social interaction, and motivation. An experimental study was conducted with 80 university students divided into control and experimental groups. The findings show that the microgroup method promotes active participation, peer learning, and motor development. These results demonstrate its importance as an effective strategy for physical education in modern academic settings.